The nursing professional's role in breastfeeding: an integrative literature review (Research, Society and Development, 2023)
The present study aimed to conduct an integrative literature review to analyze the role of the nursing professional in breastfeeding, identifying his/her contributions, best practices, challenges, and available scientific evidence. A systematic search was conducted in electronic databases, selecting studies published in the last ten years that addressed the role of the nursing professional in the context of breastfeeding. The results indicated that the nursing professional plays a key role in promoting, supporting, and encouraging breastfeeding. Best practices identified include providing evidence-based information and guidance, establishing a bond of trust with mothers, creating supportive environments, and multidisciplinary collaboration. However, challenges to be addressed were identified, such as lack of adequate time and the influence of cultural beliefs. These findings highlight the need for investments in the continuing education of the nursing professional, as well as strategies to overcome the challenges and promote breastfeeding as an extremely important health practice.